Empirical Estimation of Desired Speed Distributions for Microscopic Traffic Simulation. Issue 1 (January 2015) - Geistefeldt, Justin
The desired speed is an important parameter for microscopic traffic simulation. The desired speed can only be directly measured for free-flowing vehicles. However, the average speeds of unimpeded vehicles are systematically lower than the desired speeds of all vehicles. Recently, a new estimation technique in which the speeds of impeded vehicles were considered as censored values was introduced. Here, this method was applied with empirical traffic data in a modified version to estimate desired-speed distributions for two freeway sections in Germany. On the basis of simulation studies the method was shown to deliver consistent desired-speed distributions that allowed for a realistic representation of driver speed behavior within microscopic traffic simulation models.